2005
DOI: 10.1111/j.1540-8167.2005.00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics and Autonomic Control of Heart Rate Turbulence

Abstract: Delayed sympathetically mediated vasomotor response to VPC produces systolic blood pressure overshoot. This subsequently induces vagally mediated late heart rate deceleration. Under physiologic conditions, there is no evidence of other hemodynamic and/or mechanical effect outside the autonomic reflex arch. In patients with LV dysfunction, both depressed vagal and sympathetic modulation and, indirectly, enhanced postextrasystolic potentiation account for attenuated HRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…Frequent and persistent exposure to PVCs is associated with complex transient alterations in intracellular calcium and membrane ionic currents, heart rate dynamics, hemodynamic parameters, and both myocardial and peripheral vascular autonomic stimulation and inhibition. [35][36][37][38] Morphological and functional abnormalities of the ventricular myocardium and outflow tracts may be found on MRI in patients with apparently idiopathic PVCs, albeit this does not necessarily have a clinical implication. Bogun et al 15 postulated that ventricular dyssynchrony and increased oxygen consumption may be possible patho- Figure 1.…”
Section: Mechanisms and Pathophysiologymentioning
confidence: 99%
“…Frequent and persistent exposure to PVCs is associated with complex transient alterations in intracellular calcium and membrane ionic currents, heart rate dynamics, hemodynamic parameters, and both myocardial and peripheral vascular autonomic stimulation and inhibition. [35][36][37][38] Morphological and functional abnormalities of the ventricular myocardium and outflow tracts may be found on MRI in patients with apparently idiopathic PVCs, albeit this does not necessarily have a clinical implication. Bogun et al 15 postulated that ventricular dyssynchrony and increased oxygen consumption may be possible patho- Figure 1.…”
Section: Mechanisms and Pathophysiologymentioning
confidence: 99%
“…Numerous studies investigated the relationship between baroreflex and HRT phenomenon [5,7,9,13,14,24]. Although the degree of correlation varied with the different baroreflex techniques, all of these studies confirmed the relationship.…”
Section: Discussionmentioning
confidence: 58%
“…They documented good correlation between HRT-and BRS parameters. In a recent report, Wichterle et al [24] calculated baroreflex gain from the five post-extrasystolic cycles, which also served for TS calculations. This gain showed good correlation not only with the TS, but also with another spontaneous baroreflex index, the transfer function modulus in the low frequency (0.05-0.15 Hz) band.…”
Section: Discussionmentioning
confidence: 99%
“…TO denotes the acceleration of sinus rate immediately after a ventricular premature beat and is known to be due to vagal withdrawal (26). Delayed sympathetically mediated vasomotor response to the initial loss of cardiac output after ventricular extrasystole produces systolic blood pressure overshoot that subsequently induces vagally mediated late heart rate deceleration.…”
Section: Discussionmentioning
confidence: 99%